Cell viability and cytotoxicity assays: Biochemical elements and cellular compartments - Khalef, Lefsih; Lydia, Radja; Filicia, Khettar; Moussa, Berkoud (Cell biochemistry and function, 2024)
Cell viability and cytotoxicity assays play a crucial role in drug screening and evaluating the cytotoxic effects of various chemicals. The quantification of cell viability and proliferation serves as the cornerstone for numerous in vitro assays that assess cellular responses to external factors. In the last decade, several studies have developed guidelines for defining and interpreting cell viability and cytotoxicity based on morphological, biochemical, and functional perspectives. As this domain continues to experience ongoing growth, revealing new mechanisms orchestrating diverse cell cytotoxicity pathways, we suggest a revised classification for multiple assays employed in evaluating cell viability and cell death. This classification is rooted in the cellular compartment and/or biochemical element involved, with a specific focus on mechanistic and essential aspects of the process. The assays are founded on diverse cell functions, encompassing metabolic activity, enzyme activity, cell membrane permeability and integrity, adenosine 5′‐triphosphate content, cell adherence, reduction equivalents, dye inclusion or exclusion, constitutive protease activity, colony formation, DNA fragmentation and nuclear splitting. These assays present straightforward, reliable, sensitive, reproducible, cost‐effective, and high‐throughput approaches for appraising the effects of newly formulated chemotherapeutic biomolecules on the cell survival during the drug development process. Significance statement Various perspectives exist regarding the definitions of cell viability, cell death, and cytotoxicity. This review article aims to provide an up‐to‐date classification of commonly used in vitro cytotoxicity assays. The goal is to provide an in‐depth exploration of their underlying principles, the biochemical components involved, the specific cellular compartments targeted, and a comprehensive analysis of their respective strengths and limitations. Potential false positive results exists in cytotoxicity assessments. For instance, when there is a decrease in viability following a proliferation assay, the utilization of mandatory cell death confirmation assays. Therefore, meticulous consideration of the specific mechanisms underlying cell death, along with the incorporation of appropriate confirmation assays, becomes imperative in ensuring the accuracy and reliability of cytotoxicity assessments.